Menstrual cycle disorders in female volleyball players. (July 2013) - Wodarska, M.; Witkoś, J.; Drosdzol-Cop, A.; Dąbrowska, J.; Dąbrowska-Galas, M.; Hartman, M.; Plinta, R.; Skrzypulec-Plinta, V.
<x xml:space="preserve">Abstract</x> The aim of this study was to examine the relation between increased physical activity and menstrual disorders in adolescent female volleyball players. The study was conducted on 210 Polish female volleyball players, aged 13–17 years, the authorship questionnaire was used. The results of the study showed that irregular menstruation occurred in 19% of girls, spotting between menstrual periods in 27% and heavy menstruation was reported in 33% of girls. Out of all volleyball female players participating in the study, 94 girls (45%) declared absence of menstrual periods after regular cycles. Statistical analysis showed that the more training hours per week, the bigger probability of the occurrence of irregular menstruation. It was concluded that the number of hours of volleyball training per week affects regularity of menstrual cycles in female volleyball players. The absence of menstruation might be caused by the duration of training per week or years of training.